2016
DOI: 10.1038/srep35996
|View full text |Cite
|
Sign up to set email alerts
|

DPDR-CPI, a server that predicts Drug Positioning and Drug Repositioning via Chemical-Protein Interactome

Abstract: The cost of developing a new drug has increased sharply over the past years. To ensure a reasonable return-on-investment, it is useful for drug discovery researchers in both industry and academia to identify all the possible indications for early pipeline molecules. For the first time, we propose the term computational “drug candidate positioning” or “drug positioning”, to describe the above process. It is distinct from drug repositioning, which identifies new uses for existing drugs and maximizes their value.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 53 publications
1
13
0
1
Order By: Relevance
“…The 3D structural file or SMILES string was submitted to the PharmMapper (http://lilab-ecust. cn/pharmmapper/) [55], DRAR-CPI (http://cpi.bio-x.cn/drar/) [56], DPDR-CPI (http://cpi.bio-x.cn/ dpdr/) [57], TargetNet (http://targetnet.scbdd.com/) [58], and ChemMapper (http://lilab-ecust.cn/ chemmapper/) [59] servers to predict the targets of stemazole. Homo sapiens was chosen as the organism.…”
Section: Virtual Screening Of Drug Targetsmentioning
confidence: 99%
“…The 3D structural file or SMILES string was submitted to the PharmMapper (http://lilab-ecust. cn/pharmmapper/) [55], DRAR-CPI (http://cpi.bio-x.cn/drar/) [56], DPDR-CPI (http://cpi.bio-x.cn/ dpdr/) [57], TargetNet (http://targetnet.scbdd.com/) [58], and ChemMapper (http://lilab-ecust.cn/ chemmapper/) [59] servers to predict the targets of stemazole. Homo sapiens was chosen as the organism.…”
Section: Virtual Screening Of Drug Targetsmentioning
confidence: 99%
“…Like molecular docking scores, computing structural fingerprints requires no more information than the structures. We generated seven different types of structural fingerprints used in our previous work [25] to serve as baselines for comparison of our molecular docking model. The seven structural fingerprints are E-state, Extended Connectivity Fingerprints (ECFP)-6, Functional-Class Fingerprints (FCFP)-6, Fingerprint 4 (FP4), Klekota-Roth method, Molecular ACCess System (MACCS) and PubChem structural descriptors (labeled E-state, ECFP6, FCFP6, FP4, KR, MACCS and PubChem, respectively).…”
Section: Development and Evaluation Of Machine Learning Modelsmentioning
confidence: 99%
“…With recent increases in computing power, machine learning has played an important role in healthcare data analysis and prediction. In previous studies, we utilized machine learning models to predict drug indications [25] and drug-drug interactions [17] based on the drug-target binding profiles generated from molecular docking. We showed that the chemical-protein interactome (CPI), a collection of drugtarget binding profiles simulated with molecular docking, can be used to both predict drug pharmacologic actions and to provide possible biologic explanations for them.…”
Section: Introductionmentioning
confidence: 99%
“…Several webservers are available for target fishing [ 12 ], i.e. to try to identify a protein target for a given compound, and thus can be applied to drug repositioning [ 13 15 ]. Yet, to the best of our knowledge, the only webserver that provides a prepared virtual library of approved drugs (1852 molecules approved by the FDA between 1939 and 2017) and a facility to screen these compounds over the users' selected protein target is the e-Drugs3D webserver [ 16 ].…”
Section: Introductionmentioning
confidence: 99%